2016
DOI: 10.1051/matecconf/20165704005
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT of hydrocolloids on the quality evaluation of flour based noodles from Horse Chestnut

Abstract: Abstract. The present study was focused to investigate the effects of hydrocolloids (guar gum and xanthan gum) at additional levels (1%, 2% and 3%) on the noodle characteristics prepared from horse chestnut flour. The qualities of noodles prepared from horse chestnut flour were compared with wheat flour based noodles in terms of cooking characteristics, textural and sensory properties. The hydrocolloid addition in noodles resulted in improvement of cooking and textural qualities in consistent to control sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…For instance, the addition of 2% guar gum to corn flour noodle formulation can increase water absorption capacity from 6 to 6.86 g/g (Udachan & Sahoo, 2017). Similarly, Rafiq et al (2016) reported that the addition of 2% guar gum to horse chestnut flour noodle formulations increased water absorption by 16%.…”
Section: Water Absorption Of Analog Ricementioning
confidence: 94%
See 2 more Smart Citations
“…For instance, the addition of 2% guar gum to corn flour noodle formulation can increase water absorption capacity from 6 to 6.86 g/g (Udachan & Sahoo, 2017). Similarly, Rafiq et al (2016) reported that the addition of 2% guar gum to horse chestnut flour noodle formulations increased water absorption by 16%.…”
Section: Water Absorption Of Analog Ricementioning
confidence: 94%
“…The flour mixture was supplemented with STPP at 0.3% and 0.5% concentrations (Obadi et al, 2022;Zhao et al, 2022) as well as guar gum at 0.5% and 2% (Rafiq et al, 2016) after steaming. These concentrations can significantly reduce cooking loss in noodles.…”
Section: Analog Rice Makingmentioning
confidence: 99%
See 1 more Smart Citation